Pengaruh Metode Collaborative Learning terhadap Keterampilan Menulis Karangan Narasi - Wirda Linda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of using collaborative learning methods on narrative essay writing skills. This type of research is quantitative using the experimental method. In this study two classes were used, namely the experimental class and the control class, the experimental class was the deliberate class given a set of treatments by applying collaborative learning methods while the control class as the comparison class applied the conventional method. The results of the study, collaborative learning methods influence the writing skills of narrative essays in the experimental class, this is evidenced by the change in the value of students, which at the time of pre-test the average/mean is 74.8. After applying collaborative learning methods in the learning process in the experimental class, changes in student learning outcomes were obtained at post-test with an average value of 82.4. In conclusion, there is a significant difference between the results of narrative essay writing skills between collaborative learning methods and conventional methods. Keywords: Collaborative Learning, Narrative Writing Skills